ACTR-23. SAFETY OF INTRA-ARTERIAL CHEMOTHERAPY WITH OSMOTIC OPENING OF THE BLOOD-BRAIN BARRIER. (5th November 2018) - Priest, Ryan; Ambady, Prakash; Neweult, Edward
Abstract: Intra-arterial (IA) infusion of hypertonic mannitol transiently opens the blood-brain barrier (BBB) to improve drug delivery to intracerebral tumors. The aim of this study was to evaluate the safety of osmotic BBB disruption (BBBD) followed by administration of IA chemotherapy. We performed a retrospective chart review of all malignant brain tumor patients who underwent BBBD on six IRB approved treatment protocols or off protocol at Oregon Health and Science University between 1997 and 2017. Toxicities and adverse events (AEs), including death within 30 days of treatment, were assessed. A total of 4018 BBBD procedures were performed on 268 patients (mean 15 BBBD procedures per patient). The most common pathologies were primary central nervous system lymphoma (32%) and anaplastic oligodendroglioma (12%). Most AEs were chemotherapy-related. Only 5% of AEs were attributable to the BBBD procedure, and only 0.42% of these were associated with permanent neurological damage (Grade 3 or 4 SAE). Four SAEs were due to ischemia as detected on magnetic resonance imaging and had minimal impact on quality of life. Four SAEs were due to anterior cord syndrome subsequent to iatrogenic laminar flow of the chemotherapy and were partially responsive to steroids. Subsequently this toxicity was eliminated by procedures to avoid laminar flow. Focal seizures, largely responsive to medical intervention, occurred within 24 hours after 257 (6.4%) BBBD procedures. Most seizures (229, 89%) followed IA administration of methotrexate and were transient and without sequelae. Five patient deaths occurred within 30 days; 1 due to a brain stem stroke related to BBBD, 1 due to a pulmonary embolus, and 3 due to disease progression. We conclude that although the BBBD procedure is invasive, permanent toxicities or death are rare. These results show that osmotic BBBD can be performed safely in brain tumor patients.